Comparison Analysis of Classification Model Performance in Lung Cancer Prediction Using Decision Tree, Naive Bayes, and Support Vector Machine - Dewi Widyawati; Amaliah Faradibah; Lestari Lokapitasari Belluano, Poetri (yocto brain, 2023)
This research aims to analyze the performance of three classification models, namely Decision Tree Classifier, Support Vector Machine, and Naive Bayes Classifier, in predicting lung cancer using the